GLOBALISASI : BEBERAPA PENDEKATAN SAINS SOCIAL - Rosazman Hussin, author; Balakrishnan Parasuraman, author; Paul Porodong, author; Asmady Idris, author; Dullah Mulok, author (Kuala Lumpur : Dewan Bahasa dan Pustaka, 2000)
Includes bibliographical references and index.